A qualitative study of life events and psychological needs underlying the decision to have cosmetic surgery. (January 2017) - Locatelli, Katia; Boccara, David; De Runz, Antoine; Fournier, Mathilde; Chaouat, Marc; Villa, François; Mimoun, Maurice
Objective: A thorough psychological assessment of patients requesting cosmetic surgery can help to protect them from the risk of postoperative dissatisfaction and the onset and/or aggravation of psychiatric disorders. This study seeks to shed more light on why people desire cosmetic surgery and thus help surgeons, psychiatrists, and psychologists to conduct assessments before surgery. Methods: In-depth interviews were conducted with 35 subjects who requested cosmetic surgery. The interviews were recorded and transcribed and then analyzed qualitatively with Grounded Theory. Themes and categories were identified and compared in logical order, to build a consistent theoretical model. Results: In each interview, we identified one or more recent events that the subjects considered to be contributing factors in their decisions to have cosmetic surgery. We observed that 33 of 35 patients said they sought cosmetic surgery at a time when they were experiencing, or had just experienced, one or more major changes in their bodies or their relationships. Recent life events triggered or strengthened specific psychological needs in the subjects: to cope with the past and with change, attain a consistent identity, find or regain a positive self-image, alter others' perceptions, define themselves in relation to others, or please themselves or others. Patients said that they chose plastic surgery to fulfill one or more of these needs. Conclusions: This study identifies the role of recent events in inciting individuals to resort to cosmetic surgery. This factor provides new perspectives for surgeons to understand those patients and opens new avenues for research.